Complete mitochondrial genome and phylogenetic analysis of the Atrato slider, Trachemys medemi (Testudines, Emydidae) - Sebastián Cuadrado-Ríos; Mario Vargas-Ramírez; Christian Kehlmaier; Uwe Fritz (ZooKeys)
The mitochondrial genome of three Trachemys medemi was sequenced and annotated for the first time. The mitochondrial genome is a circular DNA molecule of 16,711–16,810 bp in size, with 60.9% AT content. It includes 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and the non-coding control region. The genome composition is characterized by a positive AT skew (0.123) and a negative GC skew (-0.342). Phylogenetic analyses based on complete mitogenomes, which lack some Trachemys species, placed T. medemi as sister to T. venusta. Phylogenies from the same dataset, but including available shorter mtDNA information for most Trachemys species, recovered T. medemi as sister to T. dorbigni, and this clade was sister to T. venusta, T. yaquia, and T. ornata. The newly obtained data are valuable for future mitogenomic investigations on Trachemys. Furthermore, our results underline the impact of incomplete taxon sampling.